2022
DOI: 10.1111/jfbc.14225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation with polyphenol extract of Thymus atlanticus on paraoxonase‐1 activity, insulin resistance, and lipid profile in high‐fat diet‐fed hamsters

Abstract: The consumption of high-fat diets is associated with oxidative stress and metabolic disorders, such as hyperlipidemia and insulin resistance (Duan et al., 2018). Hyperlipidemia causes oxidative stress as a consequence of increased reactive oxygen species (ROS) production during mitochondrial fatty acid β-oxidation (Lian et al., 2020). Most studies have reported that oxidative conditions are associated with several diseases and, together with hyperlipidemia, constitute two major factors involved in atherosclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Studies have shown that polyphenol-rich extracts of Thymus atlanticus ameliorated Triton-induced acute hyperlipidemia in rats, hamsters, and mice [ 41 , 42 , 43 ]. Thymus atlanticus polyphenol-rich extracts were also found to be efficacious in reducing hyperlipidemia, notably total cholesterol and LDL-cholesterol levels, in chronically high-fat diet-treated hamsters [ 44 ]. The anti-hyperlipidemic effect of the Thymus atlanticus polyphenol-rich extract was partially explained by its ability to inhibit cholesterol biosynthesis, as reflected by the reduction in the hepatic expression of HMG-CoA reductase observed in chronically high-fat diet-treated hamsters [ 45 ].…”
Section: Benefits Of Thymus Atlanticus On Huma...mentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that polyphenol-rich extracts of Thymus atlanticus ameliorated Triton-induced acute hyperlipidemia in rats, hamsters, and mice [ 41 , 42 , 43 ]. Thymus atlanticus polyphenol-rich extracts were also found to be efficacious in reducing hyperlipidemia, notably total cholesterol and LDL-cholesterol levels, in chronically high-fat diet-treated hamsters [ 44 ]. The anti-hyperlipidemic effect of the Thymus atlanticus polyphenol-rich extract was partially explained by its ability to inhibit cholesterol biosynthesis, as reflected by the reduction in the hepatic expression of HMG-CoA reductase observed in chronically high-fat diet-treated hamsters [ 45 ].…”
Section: Benefits Of Thymus Atlanticus On Huma...mentioning
confidence: 99%
“…Moreover, the polyphenol extract of Thymus atlanticus was found to inhibit the production of monocyte chemoattractant protein 1 (MCP-1) by macrophage cultures activated by lipopolysaccharides in a dose-dependent manner [ 34 ]. Interestingly, paraoxonase-1, a well-known molecule playing a central role in protecting arteries against atherosclerosis [ 49 ], was found to be ameliorated in association with decreased lipid peroxidation in the polyphenol extract of Thymus atlanticus combined with fat-diet-treated hamsters [ 44 ]. These effects could be mediated by rosmarinic acid and apigenin.…”
Section: Benefits Of Thymus Atlanticus On Huma...mentioning
confidence: 99%
See 2 more Smart Citations